The Problem of Time in Ethnographic Health Care Research - Willis, Eileen M. (Qualitative health research, 2010)
Drawing on the ideas outlined by anthropologist Fabian and feminist scholars Halford, Savage, and Witz, in this article I make two arguments that challenge ethnography’s claim to theoretical inference and empirical generalization, particularly for research examining contemporary health care practices. For Fabian, the dilemma arose out of ethnography’s origins in the secularization of time. Accounts of the subject’s experiences using present tense assume no progress; accounts using past tense freeze the subjects in the past. For Halford and her colleagues, the methodological problem was reversed. Their respondents were engaged in a battle with health systems in constant change that resulted in the loss of memory of a corporate past. The problem now for the ethnographer, as in many other research approaches, is one of verification of observations and reliability of interpretations. The ethnographer now becomes frozen in time as is his or her account of events in the field. Drawing on ethnographic research in hospital workplace change, in this article I examine these time-based implications for truth claims.